Development of Higher Order Thinking Skill (HOTS) Test Instruments based on Wondershare Quiz Creator - Devi Apriliana Amesa Putri M.; Maryani Maryani; Pramudya Dwi Aristya Putra (Jurnal Pembelajaran Fisika, 2021)
Critical thinking students can be improved by making questions in the test instrument categorized as Higher Order Thinking Skill (HOTS), because students are given HOTS category questions, it will train students in high-level problem-solving. This research develops a test instrument in the category of Higher Order Thinking Skill (HOTS) based on Wondershare Quiz Creator because it can train students to use the development of Science and Technology. The purpose of this development research is to develop a test instrument based on Wondershare Quiz Creator to know the completeness of student learning outcomes and the critical thinking of students. This research used Research and Development (R & D) type and the sample as many as 35 students of XII MIPA 4 in SMAN 1 Tanggul. This design research used Plomp and Nieveen's development style. Product testing is carried out online using the test instrument software that has been developed. The test instrument developed was declared valid and could be used in learning, from 35 students, there are 5 students who have completed their learning outcomes, and there are 2students who have very high critical thinking skills.Keywords: Completeness learning outcomes, Critical thinking skills, Higher Order Thinking Skill (HOTS), Test instrumentDOI: http://dx.doi.org/10.23960/jpf.v9.n1.202104